The Effect of Using Six Sigma Methodology Standards in Improving the Performance of the Internal Control System: A field study on government units in Algezira state - د. علي خليفه الشيخ عبد الله; د. ياسر تاج السر محمد سند (White Nile Journal for Studies and Research, 2020)
The study examined the effect of using Six Sigma methodology standards in improving the performance of the internal control system: A field study on government units in Algezira state, The problem of the study was that there were many administrative and financial irregularities and fraud and embezzlement cases of public and private funds, which calls for the importance of improving the performance of the internal control system, The study aimed to identify the impact of Six Sigma in improving the performance of internal control system in government units in Algezira state, And to achieve the study objectives we were tested some hypotheses. The study used the descriptive analytical method and the questionnaire collect data related to the study problem. The research reached many results proved the validity of the hypotheses, The study recommended, The senior leadership should adopt the use of Six Sigma standards to improve the performance of the internal control system in the government units in Algezira state. Key words: Six Sigma, Internal control system